Didactic support in the study of potential slovotvoobrazovatelnogo indeclinable noun in the context of the course «Contemporary ukrainian literature language» (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2013)
The article is an attempt to develop a didactic support in the study of word-formation potential of indeclinable nouns in the maintenance of discipline «Modern Ukrainian literary language». The system proposed by the task aims to explore the potential of word-formation indeclinable nouns following areas: 1) the particular entry indeclinable words in the word-formation system of the Ukrainian language, and 2) consideration of indeclinable nouns as the formative basis for suffixed units, and 3) indeclinable nouns as components of compound words.
Keywords: indeclinable words; derivative; word-formation potential; future teachers of philology special